Swot Analysis Approach To MSME Development - Ade Risna Sari; Mashudi Hariyanto; Bunga Aditi; Olga Theolina Sitorus; Annisha Suvero Suyar (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Development in the era of globalization depends heavily on the economic sector as a measure of government success. The role of society in national development especially in economic development is micro, small and medium-sized enterprises. (UMKM). SWOT analysis is the right way to solve problems in marketing management. This analysis is based on logic that can maximize strengths and opportunities, but at the same time can minimize weaknesses and threats. This research method was carried out using survey methods with interviews and quizzes on UMKM perpetrators in Cinunuk Village in particular in RW 25. Data collection is carried out by disseminating quizzes and conducting direct interviews with UMKM enterprises. Each of them has its own weaknesses and shortcomings. There are 4 problems: lack of technology mastery, not using product branding, has not used e-payment, and the location of UMKM is not listed on Google maps.